Composition, sheet and method for producing same
A composition with high filler content and spherical silica particles addresses the challenge of forming sheets with low transmission loss and expansion rates, achieving superior electrical performance for high-frequency applications.
Patent Information
- Application Number
- JP2023208911
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-11-02
- Filing Date
- 2023-12-12
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2043-12-12
AI Technical Summary
Existing high-frequency print wiring boards require materials with low transmission loss and low line expansion rates, but achieving this with high filler content has been challenging due to difficulties in forming sheets from compositions containing fluororesin and fillers.
A composition comprising 75 to 96.5% filler content by mass, primarily spherical silica particles, with other components at 10% or less, is used, allowing for a powdered rolling process to create sheets with low dielectric loss and expansion rates.
The solution provides sheets with excellent electrical characteristics, low dielectric rates, and low line expansion rates, suitable for high-frequency applications.
Smart Images

Figure 0007626955000001 
Figure 0007626955000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to compositions, sheets and methods of making the same. [Background technology]
[0002] There is a demand for high-frequency printed wiring boards with small transmission loss. It is known that fluororesin films are used in such high-frequency printed wiring boards (Patent Document 1, etc.). In addition, Patent Documents 2 to 4 describe the use of fluororesin containing filler as a wiring board material. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-8260 A [Patent Document 2] Japanese Patent Application Publication No. 63-259907 [Patent Document 3] International Publication No. 2021 / 024883 [Patent Document 4] International Publication No. 2021 / 235460 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present disclosure is to provide a composition for obtaining a sheet having a low linear expansion coefficient while maintaining electrical properties, as well as a sheet using the same and a method for producing the same. [Means for solving the problem]
[0005] The present disclosure is characterized in that the content of the filler is 75 to 96.5 mass% of the total amount of the fluororesin particles and the filler, the filler contains silica, titanium oxide, magnesium oxide, or a combination thereof, and the content of components other than the fluororesin particles and the filler is 10 mass% or less. For powder rolling molding It is a composition.
[0006] The fluororesin particles are preferably non-melt processable. The fluororesin particles are preferably made of polytetrafluoroethylene (PTFE). The polytetrafluoroethylene preferably has a standard specific gravity (SSG) of 2.0 to 2.3.
[0007] before The filler is preferably one whose surface is coated with a silane coupling agent. The filler is preferably spherical. The average particle size of the spherical filler is preferably 0.1 to 10 μm.
[0008] The fluororesin particles preferably have an average particle size of 0.05 to 1000 μm.
[0009] The present disclosure relates to a composite material that includes fluororesin particles and a filler, the content of the filler being 75 to 96.5% by mass of the total amount of the fluororesin particles and the filler, the filler including silica, titanium oxide, magnesium oxide, or a combination thereof, the content of components other than the fluororesin particles and the filler being 10% by mass or less, and that does not include a fiber reinforcing material. For powder rolling molding It is also a sheet or film characterized by being made of the composition. The thickness is preferably 5 to 250 μm. It is preferable that the relative dielectric constant (Dk) at 10 GHz is 3.5 or less, the dielectric loss tangent (Df) is 0.0014 or less, and the coefficient of linear expansion (CTE) is 40 ppm / K or less.
[0010] The present disclosure relates to a method for producing a fluororesin particle-based composite material comprising: mixing fluororesin particles with a filler containing silica, titanium oxide, magnesium oxide, or a combination thereof such that the content of the filler is 75 to 96.5% by mass of the total amount of the fluororesin particles and the filler, and such that the content of components other than the fluororesin particles and the filler is 10% by mass or less. Powder rolling molding The method for producing the sheet or film also includes a step of forming a film. It is preferable to form the film using a composition substantially consisting of fluororesin particles and a filler.
[0011] The present disclosure also relates to a metal laminate having as essential layers a metal layer and the above-mentioned sheet or film. The metal layer is preferably a copper foil. The present disclosure also relates to a circuit board having the above-mentioned metal laminate. Effect of the Invention
[0012] A sheet obtained from the composition of the present disclosure has excellent performance, such as a low linear expansion coefficient while maintaining electrical properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present disclosure will be described in detail below. Many studies have been conducted on compositions in which a fluororesin is mixed with a filler. On the other hand, in the field of high frequency printed wiring boards, increasingly high standards of performance, such as low dielectric constant, low loss and low expansion, have been required in recent years.
[0014] In the present disclosure, a composition having a low linear expansion coefficient is obtained by increasing the filler content. The composition of the present disclosure is characterized in that it contains fluororesin particles and a filler, and the filler content is 67 to 96.5 mass% of the total amount of the fluororesin particles and the filler. By using this amount, it is possible to provide a sheet having excellent performance, that is, a low linear expansion coefficient while maintaining electrical properties such as a low dielectric constant and low loss.
[0015] In the past, when a sheet was produced from a mixed composition of a fluororesin and a filler, a processing aid was added, the paste was extruded, and the extruded product was rolled into a sheet. In this method, when the filler content was high, it was difficult to extrude the paste, and it was not possible to form a sheet. In the present disclosure, it has been found that even compositions with a high filler content (67 to 96.5 mass%) can be formed into sheets by powder rolling molding. As a result, as described above, a composition with a low linear expansion coefficient can be obtained by increasing the filler content, and further, a fluororesin sheet with a low linear expansion coefficient while maintaining electrical properties can be provided.
[0016] The composition of the present disclosure contains fluororesin particles and a filler, and the content of the filler is 67 to 96.5 mass % of the total amount of the fluororesin particles and the filler. The lower limit of the filler content is more preferably 68% by mass or more, even more preferably 70% by mass or more, and most preferably 75% by mass or more. The upper limit of the filler content is preferably 90% by mass or less, and even more preferably 85% by mass or less. This content is preferable in that it is possible to lower the linear expansion coefficient while maintaining electrical properties. If the filler content is less than the lower limit, the linear expansion coefficient becomes high, and if it exceeds the upper limit, there is a problem that the sheet becomes brittle and formability deteriorates. In addition, the linear expansion coefficient should not be too low, and is most preferably 75 to 85% by mass from the viewpoint of being the same as that of the metal to be laminated, for example, copper foil.
[0017] (Filler) The filler that can be used in the present disclosure is not particularly limited, and examples thereof include organic fillers that are one or more selected from aramid fibers, polyphenyl esters, polyphenylene sulfide, polyimides, modified polyimides, polyether ether ketones, polyphenylenes, polyamides, and wholly aromatic polyester resins, and inorganic fillers that are one or more selected from ceramics, talc, mica, aluminum oxide, zinc oxide, tin oxide, titanium oxide, silicon oxide, calcium carbonate, calcium oxide, magnesium oxide, potassium titanate, glass fibers, glass chips, glass beads, silicon carbide, calcium fluoride, boron nitride, barium sulfate, molybdenum disulfide, and potassium carbonate whiskers. Two or more of these may be used in combination. Among these, fillers containing silica, titanium oxide, magnesium oxide, or a combination thereof are particularly preferred. These fillers themselves have low linear expansion coefficients and dielectric loss tangents, and therefore, when processed into compositions and sheets, Where This is also preferable because the linear expansion coefficient is low and the dielectric loss tangent (Df) can be controlled to be low.
[0018] The shape of the filler is not particularly limited, but it is particularly preferred that the filler is spherical. A spherical shape is preferred because it is easy to process uniformly during drilling, has a small specific surface area, and has low transmission loss. In particular, it is most preferred to use spherical silica particles.
[0019] The spherical filler means that the particle shape is close to a perfect sphere, and specifically, the sphericity is preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, and most preferably 0.95 or more. The sphericity is calculated by taking a photograph with an SEM and calculating the value from the area and perimeter of the observed particle as (sphericity) = {4π x (area) ÷ (perimeter) 2}. The closer to 1, the closer to a perfect sphere. Specifically, the average value measured for 100 particles using an image processing device (Spectris Corporation: FPIA-3000) is used.
[0020] In the present disclosure, the filler preferably has an average particle size of 0.1 to 10 μm. The average particle size here is the D50 value measured by a laser diffraction particle size distribution analyzer. If the average particle size is less than 0.1 μm, the filler tends to aggregate, making it difficult to obtain a sufficient effect. If the average particle size exceeds 10 μm, the sheet tends to be difficult to form into a thin film.
[0021] The spherical silica particles used in the present disclosure preferably have a D90 / D10 of 2 or more (preferably 2.3 or more, 2.5 or more) and a D50 of 10 μm or less when the volume is accumulated from the smallest particle diameter. Furthermore, it is preferable that the D90 / D50 is 1.5 or more (more preferably 1.6 or more). It is preferable that the D50 / D10 is 1.5 or more (more preferably 1.6 or more). Since the small particle diameter spherical silica particles can enter the gaps between the large particle diameter spherical silica particles, it is possible to achieve excellent filling properties and high fluidity. In particular, it is preferable that the particle size distribution has a higher frequency on the side of small particle diameters compared to a Gaussian curve. The particle size can be measured by a laser diffraction scattering type particle size distribution measuring device. It is also preferable that coarse particles having a particle size of a certain size or more are removed by a filter or the like.
[0022] The above-mentioned spherical silica particles preferably have a water absorption of 1.0% or less, more preferably 0.5% or less. The water absorption is based on the mass of the silica particles when dry. The water absorption is measured by leaving a sample in a dry state at 40°C and 80% RH for 1 hour, and measuring the water generated by heating at 200°C using a Karl Fischer water content meter, and calculating the water absorption.
[0023] The spherical silica particles can also be measured for each of the parameters using the above-mentioned method after the fluororesin sheet is heated in an air atmosphere at 600°C for 30 minutes to burn off the fluororesin and the spherical silica particles are taken out.
[0024] The spherical silica particles may be commercially available silica particles that satisfy the above-mentioned properties. Examples of commercially available silica particles include Denka fused silica FB grade (manufactured by Denka Co., Ltd.), Denka fused silica SFP grade (manufactured by Denka Co., Ltd.), Excelica (manufactured by Tokuyama Corporation), high-purity synthetic spherical silica particles Admafine (manufactured by Admatechs Co., Ltd.), Admanano (manufactured by Admatechs Co., Ltd.), and Admafuse (manufactured by Admatechs Co., Ltd.).
[0025] The titanium oxide and magnesium oxide have a higher dielectric constant (Dk) than silica, and can be added to adjust the dielectric constant (Dk). Commercially available titanium oxides include CR-EL (manufactured by Ishihara Sangyo Kaisha, Ltd.) and HT0210 (manufactured by Toho Titanium Co., Ltd.). Commercially available magnesium oxides include RF-10CS and RF-10C-45μm (manufactured by Ube Material Industries, Ltd.).
[0026] The filler is preferably one that has been subjected to a surface treatment in advance, which can suppress aggregation of the silica particles and allow the silica particles to be well dispersed in the resin composition.
[0027] The above surface treatment can be carried out by appropriately selecting the type and amount of a surface treatment agent. The amount of the treatment is preferably 0.2% by mass or more, and more preferably 0.5% by mass or more from the viewpoint of lowering the dielectric constant, the dielectric loss tangent, and the linear expansion coefficient. The amount of the treatment is preferably 5% by mass or less. The surface treatment is not particularly limited, and any known treatment can be used.Specific examples of the surface treatment include treatment with a silane coupling agent such as epoxysilane, aminosilane, isocyanatesilane, vinylsilane, acrylicsilane, hydrophobic alkylsilane, phenylsilane, and fluorinated alkylsilane having a reactive functional group, plasma treatment, and fluorination treatment.
[0028] Specific examples of the silane coupling agent include epoxy silanes such as γ-glycidoxypropyltriethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, amino silanes such as aminopropyltriethoxysilane and N-phenylaminopropyltrimethoxysilane, isocyanate silanes such as 3-isocyanatepropyltrimethoxysilane and 3-isocyanatepropyltriethoxysilane, vinyl silanes such as vinyltrimethoxysilane, and acrylic silanes such as acryloxytrimethoxysilane.
[0029] In the present disclosure, among the fillers that have been subjected to surface treatment, it is preferable to use a filler whose surface is coated with a silane coupling agent.
[0030] (Fluororesin particles) The composition of the present disclosure contains fluororesin particles. The fluororesin particles have low dielectric properties and can therefore be suitably used for the purposes of the present disclosure.
[0031] The average particle size of the fluororesin particles is preferably 0.05 to 1000 μm. The lower limit of the average particle size of the fluororesin particles is more preferably 0.07 μm or more, and even more preferably 0.1 μm or more. The upper limit of the average particle size of the fluororesin particles is preferably 700 μm or less, and even more preferably 500 μm or less. The use of such a material has the advantage of excellent moldability and dispersibility. The average particle size here is a value measured in accordance with ASTM D 4895.
[0032] The fluororesin particles preferably have a volume-based cumulative 50% diameter of 0.05 to 40 μm. The lower limit of the volume-based cumulative 50% diameter of the fluororesin particles is more preferably 0.7 μm or more, and even more preferably 1 μm or more. The upper limit of the volume-based cumulative 50% diameter of the fluororesin particles is preferably 35 μm or less, and even more preferably 30 μm or less. The use of such a material has the advantage of excellent moldability and dispersibility. The volume-based cumulative 50% diameter here is a value measured by a laser diffraction particle size distribution analyzer.
[0033] The fluororesin particles used in the present disclosure are not particularly limited, and examples thereof include polytetrafluoroethylene (PTFE), tetrafluoroethylene [TFE] / hexafluoropropylene [HFP] copolymer [FEP], TFE / alkyl vinyl ether copolymer [PFA], TFE / HFP / alkyl vinyl ether copolymer [EPA], TFE / chlorotrifluoroethylene [CTFE] copolymer, TFE / ethylene copolymer [ETFE], polyvinylidene fluoride [PVdF], tetrafluoroethylene having a molecular weight of 300,000 or less [LMW-PTFE], etc. One type may be used, or two or more types may be mixed.
[0034] The fluororesin particles used in the present disclosure are preferably non-melt processable. "Non-melt-processable" means that the resin does not have sufficient fluidity even when heated above its melting point, and cannot be molded by the melt molding techniques commonly used for resins. PTFE falls into this category. In addition, from the viewpoint of low dielectric properties, PTFE is particularly preferable. PTFE having fibrillation properties is preferable. PTFE having fibrillation properties means PTFE in which unsintered polymer particles can be paste extruded or powder roll molded.
[0035] PTFE may be modified polytetrafluoroethylene (hereinafter referred to as modified PTFE), homopolytetrafluoroethylene (hereinafter referred to as homoPTFE), or a mixture of modified PTFE and homoPTFE. From the viewpoint of maintaining good moldability of polytetrafluoroethylene, the content of modified PTFE in the polymeric PTFE is preferably 10% by weight or more and 98% by weight or less, and more preferably 50% by weight or more and 95% by weight or less. The homo-PTFE is not particularly limited, and homo-PTFE disclosed in JP-A-53-60979, JP-A-57-135, JP-A-61-16907, JP-A-62-104816, JP-A-62-190206, JP-A-63-137906, JP-A-2000-143727, JP-A-2002-201217, WO 2007 / 046345 pamphlet, WO 2007 / 119829 pamphlet, WO 2009 / 001894 pamphlet, WO 2010 / 113950 pamphlet, WO 2013 / 027850 pamphlet, etc. can be suitably used. Among these, homo-PTFE having high stretchability and disclosed in JP-A-57-135, JP-A-63-137906, JP-A-2000-143727, JP-A-2002-201217, WO 2007 / 046345, WO 2007 / 119829, WO 2010 / 113950 and the like is preferred.
[0036] The modified PTFE is composed of TFE and a monomer other than TFE (hereinafter referred to as a modified monomer). The modified PTFE may be, but is not limited to, one that is uniformly modified by the modified monomer, one that is modified at the beginning of the polymerization reaction, one that is modified at the end of the polymerization reaction, etc. The modified PTFE is preferably a TFE copolymer obtained by subjecting a small amount of a monomer other than TFE to polymerization together with TFE within a range that does not significantly impair the properties of the TFE homopolymer. The modified PTFE may be, for example, those disclosed in JP-A-60-42446, JP-A-61-16907, JP-A-62-104816, JP-A-62-190206, JP-A-64-1711, JP-A-2-261810, JP-A-11-240917, JP-A-11-240918, WO 2003 / 033555 pamphlet, WO 2005 / 061567 pamphlet, WO 2007 / 005361 pamphlet, WO 2011 / 055824 pamphlet, WO 2013 / 027850 pamphlet, etc., which can be suitably used. Among these, modified PTFEs having high stretchability and disclosed in JP-A-61-16907, JP-A-62-104816, JP-A-64-1711, JP-A-11-240917, WO 2003 / 033555, WO 2005 / 061567, WO 2007 / 005361, WO 2011 / 055824 and the like are preferred.
[0037] The modified PTFE contains TFE units based on TFE and modified monomer units based on modified monomers. The modified monomer units are a part of the molecular structure of the modified PTFE and are derived from the modified monomer. The modified PTFE contains the modified monomer units in an amount of preferably 0.001 to 0.500 mass% of the total monomer units, more preferably 0.01 to 0.30 mass%. The total monomer units are the parts derived from all monomers in the molecular structure of the modified PTFE.
[0038] The modifying monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene (HFP), chlorofluoroolefins such as chlorotrifluoroethylene (CTFE), hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride (VDF), perfluorovinyl ethers, perfluoroalkylethylenes (PFAE), ethylene, etc. The modifying monomer used may be one type or multiple types.
[0039] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorounsaturated compounds represented by the following general formula (1). CF2 = CF-ORf (1) (In the formula, Rf represents a perfluoro organic group.)
[0040] In this specification, a perfluoro organic group is an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The perfluoro organic group may have an ether oxygen.
[0041] An example of the perfluorovinyl ether is perfluoro(alkyl vinyl ether) (PAVE) in which Rf in the above general formula (1) is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5. Examples of the perfluoroalkyl group in PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group. Preferred examples of PAVE include perfluoropropyl vinyl ether (PPVE) and perfluoromethyl vinyl ether (PMVE).
[0042] The perfluoroalkylethylene (PFAE) is not particularly limited, and examples thereof include perfluorobutylethylene (PFBE), perfluorohexylethylene (PFHE), and the like.
[0043] The modifying monomer in the modified PTFE is preferably at least one selected from the group consisting of HFP, CTFE, VDF, PAVE, PFAE and ethylene.
[0044] The PTFE used in the present disclosure may have a core-shell structure.The PTFE having a core-shell structure may include, for example, modified polytetrafluoroethylene, which contains a core of high molecular weight polytetrafluoroethylene and a shell of lower molecular weight polytetrafluoroethylene or modified polytetrafluoroethylene in a particle.As such modified polytetrafluoroethylene, for example, the polytetrafluoroethylene described in JP-A-2005-527652 may be included.
[0045] In the present disclosure, it is preferable to use such a non-melt-processable fluororesin and form it into a fluororesin sheet by a molding method that fibrillates the fluororesin. The molding method will be described later.
[0046] The PTFE preferably has a standard specific gravity (SSG) of 2.0 to 2.3. When such PTFE is used, a PTFE membrane having high strength (cohesion and puncture strength per unit thickness) is easily obtained. PTFE having a large molecular weight has a long molecular chain, and therefore it is difficult to form a structure in which the molecular chains are regularly arranged. In this case, the length of the amorphous part increases, and the degree of entanglement between the molecules increases. When the degree of entanglement between the molecules is high, the PTFE membrane is unlikely to deform under an applied load and is considered to exhibit excellent mechanical strength. In addition, when a PTFE having a large molecular weight is used, a PTFE membrane having a small average pore size is easily obtained.
[0047] The lower limit of the SSG is more preferably 2.05, and even more preferably 2.1.The upper limit of the SSG is more preferably 2.25, and even more preferably 2.2.
[0048] Standard specific gravity (SSG) was measured by preparing a sample in accordance with ASTM D-4895-89 and measuring the specific gravity of the resulting sample by the water displacement method.
[0049] The PTFE preferably has a refractive index in the range of 1.2 to 1.6. By having such a refractive index, it is preferable in terms of low dielectric constant. The refractive index can be adjusted to be within the above range by a method of adjusting the polarizability or flexibility of the main chain. The lower limit of the refractive index is more preferably 1.25, more preferably 1.30, and most preferably 1.32. The upper limit of the refractive index is more preferably 1.55, more preferably 1.50, and most preferably 1.45. The refractive index is measured using a refractometer (Abbemat 300).
[0050] In this embodiment, the molecular weight (number average molecular weight) of the PTFE constituting the PTFE particles is, for example, in the range of 2 million to 12 million. The lower limit of the molecular weight of the PTFE may be 3 million or 4 million. The upper limit of the molecular weight of the PTFE may be 10 million.
[0051] The number average molecular weight of PTFE can be measured by a method based on standard specific gravity and a method based on dynamic viscoelasticity when melted. The method based on standard specific gravity can be performed by a water displacement method based on ASTM D-792 using a sample molded based on ASTM D-4895 98. The method based on dynamic viscoelasticity is described, for example, by S. Wu in Polymer Engineering & Science, 1988, Vol. 28, 538 and the same document, 1989, Vol. 29, 273.
[0052] The particulate PTFE preferably contains 50% by mass or more, more preferably 80% by mass or more, of polytetrafluoroethylene resin having a secondary particle diameter of 500 μm or more. By containing PTFE having a secondary particle diameter of 500 μm or more within this range, it is advantageous in that a sheet with high strength can be produced. By using PTFE with a secondary particle size of 500 μm or more, a sheet with lower resistance and excellent toughness can be obtained.
[0053] The lower limit of the secondary particle diameter is more preferably 300 μm, and even more preferably 350 μm. The upper limit of the secondary particle diameter is more preferably 700 μm or less, and even more preferably 600 μm or less. The secondary particle diameter can be determined, for example, by a sieving method.
[0054] The particulate PTFE preferably has an average primary particle size of 50 nm or more, more preferably 100 nm or more, even more preferably 150 nm or more, and particularly preferably 200 nm or more, in order to obtain a sheet having higher strength and excellent homogeneity. The larger the average primary particle diameter of PTFE, the more suppressed the increase in paste extrusion pressure when the powder is used for paste extrusion molding, and the better the moldability. The upper limit is not particularly limited, but may be 500 nm. From the viewpoint of productivity in the polymerization process, it is preferably 350 nm.
[0055] The above average primary particle diameter can be determined by preparing a calibration curve of the transmittance of 550 nm projected light per unit length of an aqueous dispersion of PTFE obtained by polymerization, the polymer concentration of which is adjusted to 0.22% by mass, and the average primary particle diameter determined by measuring the unidirectional diameter in a transmission electron microscope photograph, and measuring the transmittance of the aqueous dispersion to be measured, and then based on the calibration curve.
[0056] Moreover, the PTFE preferably has a maximum endothermic peak temperature (crystalline melting point) of 340±7°C.
[0057] The PTFE may be a low-melting-point PTFE having a maximum peak temperature of 338°C or lower on the endothermic curve on a crystalline melting curve measured by a differential scanning calorimeter, or a high-melting-point PTFE having a maximum peak temperature of 342°C or higher on the endothermic curve on a crystalline melting curve measured by a differential scanning calorimeter.
[0058] The low-melting-point PTFE particles are particles produced by emulsion polymerization, and have the above-mentioned maximum endothermic peak temperature (crystalline melting point), a dielectric constant (ε) of 2.08 to 2.2, and a dielectric tangent (tanδ) of 1.9×10 -4 ~4.0×10 -4 Examples of commercially available products include Polyflon fine powders F201, F203, F205, F301, and F302 manufactured by Daikin Industries, Ltd., CD090 and CD076 manufactured by Asahi Glass Co., Ltd., and TF6C, TF62, and TF40 manufactured by DuPont.
[0059] The high melting point PTFE particles are also produced by emulsion polymerization, and have the above-mentioned maximum endothermic peak temperature (crystalline melting point), a dielectric constant (ε) of 2.0 to 2.1, and a dielectric tangent (tanδ) of 1.6×10 -4 ~2.2×10 -4 As commercially available products, for example, Polyflon Fine Powder F104 manufactured by Daikin Industries, Ltd., CD1, CD141, and CD123 manufactured by Asahi Glass Co., Ltd., and TF6 and TF65 manufactured by DuPont can be mentioned.
[0060] The average particle size of the secondary aggregate particles of both PTFE particles is usually preferably 250 to 2000 μm. In particular, granulated particles obtained by granulation using a solvent are preferred from the viewpoint of improving the flowability when filling a mold during preforming.
[0061] PTFE having a particle shape that satisfies the above-mentioned parameters can be obtained by a conventional manufacturing method. For example, it may be manufactured according to the manufacturing methods described in International Publication No. 2015-080291 and International Publication No. 2012-086710.
[0062] (composition) The composition of the present disclosure contains the above-mentioned filler and fluororesin particles. If necessary, it may contain components other than the filler and fluororesin particles, or may consist of only the filler and fluororesin particles. The content of components other than the filler and fluororesin particles is preferably 10 mass% or less based on the total amount of the composition. In particular, it is preferable for the composition to essentially consist of fluororesin particles and a filler. Here, "essentially consist of fluororesin particles and a filler" means that the content of components other than the filler and fluororesin particles is 3 mass% or less based on the total amount of the composition.
[0063] The composition of the present disclosure preferably has a 10 GHz dielectric tangent of 0.0001 to 0.0015 as the composition. Having the dielectric tangent within this range is preferable in terms of low loss.
[0064] (Sheet) The compositions of the present disclosure are suitable for use in forming sheets. The present disclosure also relates to a sheet made of a composition containing fluororesin particles and a filler, the filler content being 67 to 96.5 mass % of the total amount of the fluororesin particles and the filler.
[0065] The sheet preferably has a thickness of 5 to 250 μm. Even if the sheet of the present disclosure is thin, it can sufficiently achieve its purpose. From this viewpoint, the thickness is more preferably less than 200 μm, and even more preferably less than 150 μm.
[0066] The sheet of the present disclosure preferably has a relative dielectric constant (Dk) of 3.5 or less, a dielectric dissipation factor (Df) of 0.0014 or less, and a coefficient of linear expansion (CTE) of 40 ppm / K or less at 10 GHz. By satisfying these physical properties, the sheet has excellent electrical properties and a low linear expansion coefficient.
[0067] A relative dielectric constant (Dk) of 3.5 or less at 10 GHz is preferable in that the dielectric loss is low. The upper limit of the relative dielectric constant (Dk) is more preferably 3.2, and even more preferably 3.1. The lower limit of the relative dielectric constant (Dk) is more preferably 2.0, and even more preferably 2.5.
[0068] A dielectric loss tangent (Df) of 0.0014 or less is preferable in that the dielectric loss is low. The upper limit of the dielectric loss tangent (Df) is more preferably 0.0012, and further preferably 0.0011. The lower limit of the dielectric loss tangent (Df) is more preferably 0.
[0069] In this specification, the relative permittivity (Dk) and dielectric loss tangent (Df) at 10 GHz were determined by measuring Dk and Df at 25° C. and 10 GHz using a split cylinder type dielectric constant / dielectric loss tangent measuring device (manufactured by EM Lab).
[0070] A coefficient of linear expansion (CTE) of 40 ppm / K or less is preferable in that it results in a fluororesin sheet with low shrinkage and excellent dimensional stability. The upper limit of the coefficient of linear expansion (CTE) is more preferably 35, and even more preferably 30. The lower limit of the coefficient of linear expansion (CTE) is more preferably 5, and even more preferably 10. The linear expansion coefficient in this specification was determined by performing TMA measurement in a tensile mode using a TMA-7100 (manufactured by Hitachi High-Tech Science Corporation), using a sheet cut to a length of 20 mm and a width of 5 mm as a sample piece, setting the chuck distance to 10 mm, and determining the linear expansion coefficient from the amount of displacement of the sample at 0 to 150°C with a heating rate of 2°C / min while applying a load of 49 mN.
[0071] (Sheet manufacturing method) The sheet of the present disclosure can be obtained by forming a film using the above-mentioned fluororesin particles and filler. The production method is preferably carried out by powder rolling molding.
[0072] The present disclosure also relates to a method for producing the above-mentioned sheet, comprising the step of mixing the above-mentioned fluororesin particles and a filler so that the content of the filler is 67 to 96.5 mass% based on the total amount of the fluororesin particles and the filler, and forming a film.
[0073] As described above, it is preferable to use a non-melt processable fluororesin as the fluororesin used in the sheet of the present disclosure. When such a fluororesin is used and is molded into a sheet, it is preferable to mold the sheet by fibrillating powdered PTFE as a raw material.
[0074] Specific examples of the powder rolling molding method include the following methods.
[0075] (Powder rolling molding) Powder rolling molding is a method in which a resin powder is fibrillated by applying a shear force to the resin powder, and then molded into a sheet shape. The method may include a step of subsequently firing the powder to obtain a molded body. More specifically, A step (1) of applying a shear force to a raw material composition containing fluororesin particles and a filler while mixing the raw material composition. A step (2) of forming the mixture obtained by the step (1) into a bulk form; and A step (3) of rolling the bulk mixture obtained in the step (2) into a sheet. The manufacturing method may include the following. Furthermore, the method may include a step (4) of baking the sheet-like material obtained above at 200 to 400° C. for 1 to 60 minutes. The physical properties of the sheet can be controlled by changing the baking temperature. For example, the dielectric tangent can be reduced by baking at a low temperature of 345° C. or less, and the linear expansion coefficient can be reduced by baking at a high temperature of 350° C. or more. Additionally, step (2) may be omitted.
[0076] When a sheet is formed by such powder rolling molding, it is preferable to form a film using a composition substantially consisting of fluororesin particles and a filler. Alternatively, it is preferable to mix only the fluororesin particles and the filler and then mold the mixture.
[0077] The stirring device used in the mixing in the above step (1) is not particularly limited as long as it can mix the fluororesin particles and the filler, and examples thereof include a labo plasto mill, a single-shaft kneader, a twin-shaft kneader, a mixer (twin-shaft mixer, butterfly mixer, concentric twin-shaft mixer, pony mixer, trimix, planetary mixer, PD mixer, dissolver), a bead mill (mill, mighty mill), a roll mill (two-roll, three-roll), a kneader (flushing kneader, salt milling kneader, pressure kneader), etc. The stirring temperature is not particularly limited, but is preferably 0 to 50°C, and more preferably 10 to 30°C. The stirring time is not particularly limited, but is preferably from 1 second to 1 hour, and more preferably from 10 seconds to 10 minutes. In addition, when mixing, it is preferable to partially fibrillate the PTFE.
[0078] The device for rolling into a sheet in the above step (3) is not particularly limited, but may be any device capable of shearing the powder mixture obtained in step (1) or the bulk mixture obtained in step (2) into a sheet, and examples of such devices include a powder rolling device, a powder film forming device, a roll press (two or three rolls), and a double belt press. The temperature at which the sheet is formed is not particularly limited, but is preferably 20 to 300°C, and more preferably 30 to 200°C.
[0079] (Laminate) The sheet of the present disclosure can be used as a sheet for circuit boards by laminating it with other substrates.
[0080] The present disclosure also relates to a metal laminate having a metal layer and the above-mentioned fluororesin sheet as essential layers. The metal laminate may be characterized in that a metal layer is bonded to one or both sides of the above-mentioned fluororesin sheet. As described above, the sheet containing the fluororesin of the present disclosure is particularly suitable for use in printed wiring board applications, and therefore can be suitably used as such a metal laminate. Examples of the metal layer include copper foil, gold foil, silver foil, platinum foil, ruthenium foil, etc. Among these, copper foil is preferred because it has low conductor loss.
[0081] The copper foil preferably has an Rz of 1.6 μm or less. That is, the composition of the present disclosure has excellent adhesion to copper foil having a high smoothness of Rz of 1.6 μm or less. Furthermore, the copper foil only needs to have an Rz of 1.6 μm or less on at least the surface that is bonded to the fluororesin sheet, and the Rz value of the other surface is not particularly limited. The above Rz is the sum of the highest point (maximum peak height: Rp) and the deepest point (maximum valley depth: Rv). The above surface roughness is the ten-point average roughness defined in JIS-B0601. In this specification, the above Rz is a value measured using a surface roughness meter (product name: Surfcom 470A, manufactured by Tokyo Seiki Co., Ltd.) with a measurement length of 4 mm.
[0082] The thickness of the copper foil is not particularly limited, but is preferably in the range of 1 to 100 μm, more preferably in the range of 5 to 50 μm, and even more preferably in the range of 9 to 35 μm.
[0083] The copper foil is not particularly limited, and specific examples thereof include rolled copper foil and electrolytic copper foil.
[0084] The copper foil having Rz of 1.6 μm or less is not particularly limited, and commercially available products can be used. Examples of commercially available copper foil having Rz of 1.6 μm or less include electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Layer Powder Co., Ltd.).
[0085] The copper foil may be surface-treated to enhance the adhesive strength with the sheet of the present disclosure.
[0086] The surface treatment is not particularly limited, but may be a silane coupling treatment, a plasma treatment, a corona treatment, a UV treatment, an electron beam treatment, etc., and the reactive functional group of the silane coupling agent is not particularly limited, but from the viewpoint of adhesion to the resin substrate, it is preferable to have at least one selected from an amino group, a (meth)acrylic group, a mercapto group, and an epoxy group at the end. In addition, the hydrolyzable group is not particularly limited, but may be an alkoxy group such as a methoxy group or an ethoxy group. The copper foil used in the present disclosure may have an anti-rust layer (such as an oxide film such as chromate), a heat-resistant layer, etc. formed thereon.
[0087] The surface-treated copper foil having a surface treatment layer of the above-mentioned silane compound on the copper foil surface can be produced by preparing a solution containing the silane compound and then surface treating the copper foil with this solution.
[0088] The copper foil may have a roughening treatment layer on the surface thereof from the viewpoint of improving adhesion to a resin substrate. In addition, if there is a risk that the roughening treatment will degrade the performance required in the present disclosure, the amount of roughening particles electrodeposited on the copper foil surface can be reduced as necessary, or the roughening treatment can be omitted.
[0089] Between the copper foil and the surface treatment layer, one or more layers selected from the group consisting of a heat-resistant treatment layer, a rust-proofing treatment layer, and a chromate treatment layer may be provided in order to improve various properties. These layers may be a single layer or multiple layers.
[0090] The copper clad laminate of the present disclosure may further include layers other than the copper foil and sheet. The layers other than the copper foil and the sheet are preferably at least one selected from the group consisting of polyimide, modified polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, modified polyphenylene ether, polyphenylene ether, and polybutadiene.
[0091] The layers other than the copper foil and the sheet are not particularly limited as long as they are made of the above-mentioned resins. In addition, the layers other than the copper foil and the sheet made of fluororesin preferably have a thickness in the range of 12.5 to 260 μm.
[0092] In the metal clad laminate of the present disclosure, the metal layer may be formed on one or both sides of the rolled sheet. Methods for forming the metal layer include a method for laminating (adhering) a metal foil on the surface of the rolled sheet, a vapor deposition method, a plating method, and the like. Methods for laminating the metal foil include a method using heat pressing. The heat pressing temperature may be from the melting point of the dielectric film -150°C to the melting point of the dielectric film +40°C. The heat pressing time is, for example, 1 to 30 minutes. The heat pressing pressure may be 0.1 to 10 MPa, and the laminate may be manufactured by such a method.
[0093] (film) In the present disclosure, the composition may be used to form a film. The present disclosure also relates to a film comprising a composition containing fluororesin particles and a filler, the content of the filler being 67 to 96.5 mass% of the total amount of the fluororesin particles and the filler. The film of the present disclosure can be obtained by applying a dispersion in which a powder containing fluororesin particles and a filler are dispersed in a liquid medium onto a substrate, drying the dispersion, and then heating the applied coating.
[0094] The metal laminate of the present disclosure is not particularly limited in its application, and is used, for example, as a circuit board. The present disclosure also relates to a circuit board having the above-mentioned metal laminate. A circuit board is a plate-shaped component for electrically connecting electronic components such as semiconductors and capacitor chips while arranging and fixing them in a limited space. There is no particular limitation on the configuration of the circuit board formed from the present metal laminate. The circuit board may be any of a rigid board, a flexible board, and a rigid-flexible board. The circuit board may be any of a single-sided board, a board, a double-sided board, and a multilayer board (such as a built-up board). In particular, it can be suitably used for flexible boards and rigid boards. In particular, it can be suitably used as a printed circuit board for high frequencies of 10 GHz or more.
[0095] The circuit board is not particularly limited, and can be produced by a general method using the above-mentioned metal laminate.
[0096] The laminate for a circuit board is also a laminate characterized by having a copper foil layer, the above-mentioned sheet, and further a base layer. The base layer is not particularly limited, but preferably has a fabric layer made of glass fiber and a resin film layer.
[0097] The sheet and metal laminate of the present disclosure are used as electric and electronic components, for example, antennas used in electronic devices and communication devices such as ETC, GPS, wireless LAN, and mobile phones, high-speed transmission connectors, CPU sockets, millimeter wave and quasi-millimeter wave radars such as collision prevention radars, RFID tags, capacitors, inverter parts, cable covering materials, insulating materials for secondary batteries such as lithium ion batteries, speaker diaphragms, etc.
[0098] Examples of high-speed communication-compatible boards include base station antenna boards, antenna distribution boards, boards for RRH (Remote Radio Head) which is the radio part of a wireless base station, boards for the control part or baseband part (BBU: Base Band Unit) of a wireless base station, transceiver boards for high-speed communication, boards for RNC (Radio Network Controller), boards for high-speed transmitters, boards for high-speed receivers, boards for high-speed signal multiplexing circuits, boards for WiFig using the 60 GHz band, boards for data transfer used in servers for data centers, etc. Examples of high-speed communication-compatible boards include antenna boards, for example, boards for massive multi-element antennas (Massive MIMO) for large-capacity communication required by standards after 5G.
[0099] The sheet can be used not only as an insulator for circuit boards, but also as an insulator for signal line coating, for example, as an insulating coating material (e.g. insulating tube) for waveguides that transmit high-speed signals, QSFP cables for high-speed LANs, coaxial cables for high-speed communication (e.g. SFP+ cables, QSFP+ cables, etc.), and low-loss coaxial cables.
[0100] When using such high frequencies, materials used in electrical components such as connectors and communication devices such as casings are required to have stable electrical properties such as low relative dielectric constant (εr) and low dielectric tangent (tanδ). The sheet can also be used as an insulating material for such materials.
[0101] The sheet can also be used as an insulating material for connector printed wiring boards that require soldering. The sheet has excellent heat resistance, so problems are unlikely to occur even at high temperatures during soldering.
[0102] In dielectric waveguides, materials with low dielectric loss are required to transmit high frequency millimeter waves or submillimeter waves with low loss. The sheet can also be used as an insulating material for dielectric waveguides that transmit millimeter waves, submillimeter waves, etc. Examples of dielectric waveguides include cylindrical dielectric lines, rectangular dielectric lines, elliptical dielectric lines, tubular dielectric lines, image lines, insulator image lines, trapped image lines, rib guides, strip dielectric lines, inverted strip lines, H guides, and nonradiative dielectric lines (NRD guides).
[0103] The glass fiber fabric layer is a layer made of glass cloth, glass nonwoven fabric, or the like. The glass cloth may be commercially available, and is preferably treated with a silane coupling agent to enhance affinity with the fluororesin. The glass cloth may be made of E glass, C glass, A glass, S glass, D glass, NE glass, low dielectric constant glass, etc., and is preferably made of E glass, S glass, or NE glass because of its easy availability. The fibers may be woven in a plain weave or a twill weave. The thickness of the glass cloth is usually 5 to 90 μm, and preferably 10 to 75 μm, but it is preferable to use a glass cloth thinner than the sheet of the present disclosure.
[0104] The laminate may use a glass nonwoven fabric as a fabric layer made of glass fibers. The glass nonwoven fabric is a fabric in which short glass fibers are fixed with a small amount of a binder compound (resin or inorganic substance), or a fabric in which the shape is maintained by entangling short glass fibers without using a binder compound, and a commercially available product can be used. The diameter of the short glass fibers is preferably 0.5 to 30 μm, and the fiber length is preferably 5 to 30 mm. Specific examples of the binder compound include resins such as epoxy resins, acrylic resins, cellulose, polyvinyl alcohol, and fluororesins, and inorganic substances such as silica compounds. The amount of the binder compound used is usually 3 to 15 mass % based on the short glass fibers. Examples of the material of the short glass fibers include E glass, C glass, A glass, S glass, D glass, NE glass, and low dielectric constant glass. The thickness of the glass nonwoven fabric is usually 50 μm to 1000 μm, and preferably 100 to 900 μm. In the present disclosure, the thickness of the glass nonwoven fabric refers to a value measured in accordance with JIS P8118:1998 using a digital gauge DG-925 (load 110 grams, face diameter 10 mm) manufactured by Ono Sokki Co., Ltd. In order to increase the affinity with the fluororesin, the glass nonwoven fabric may be treated with a silane coupling agent.
[0105] Many glass nonwoven fabrics have an extremely high porosity of 80% or more, so it is preferable to use a sheet thicker than the sheet of the present disclosure and compress it under pressure before use.
[0106] The glass fiber fabric layer may be a layer in which a glass cloth and a glass nonwoven fabric are laminated together, whereby the properties of the two fabrics are combined to obtain suitable properties. The glass fiber fabric layer may be in the form of a prepreg impregnated with a resin.
[0107] In the above laminate, the glass fiber fabric layer and the sheet may be bonded at the interface, or the glass fiber fabric layer may be partially or entirely impregnated with the sheet. Furthermore, a prepreg may be prepared by impregnating a fabric made of glass fibers with the fluororesin composition. The prepreg thus obtained may be further laminated with the sheet of the present disclosure. In this case, the fluororesin composition used in preparing the prepreg is not particularly limited, and the sheet of the present disclosure may be used.
[0108] The resin film used as the substrate layer is preferably a heat-resistant resin film or a thermosetting resin film. Examples of the heat-resistant resin film include polyimide, modified polyimide, liquid crystal polymer, polyphenylene sulfide, etc. Examples of the thermosetting resin include those containing epoxy resin, bismaleimide, polyphenylene oxide, modified polyphenylene ether, polyphenylene ether, polybutadiene, etc. The heat-resistant resin film and the thermosetting resin film may contain reinforcing fibers. The reinforcing fibers are not particularly limited, but for example, glass cloth, particularly low dielectric type, is preferable.
[0109] The heat-resistant resin film and the thermosetting resin film are not particularly limited in terms of dielectric properties, linear expansion coefficient, water absorption coefficient, and other properties, but for example, the dielectric constant at 20 GHz is preferably 3.8 or less, more preferably 3.4 or less, and even more preferably 3.2 or less. The dielectric loss tangent at 20 GHz is preferably 0.0030 or less, more preferably 0.0025 or less, and even more preferably 0.0020 or less. The linear expansion coefficient is preferably 100 ppm / °C or less, more preferably 70 ppm / °C or less, and even more preferably 40 ppm / °C or less. The water absorption coefficient is preferably 1.0% or less, more preferably 0.5% or less, and even more preferably 0.1% or less. EXAMPLES
[0110] The present disclosure will now be described in detail with reference to examples. In the following examples, unless otherwise specified, "parts" and "%" represent "parts by mass" and "% by mass", respectively.
[0111] (Examples 1 to 13) (Powder rolling molding) The fluororesin particles (PTFE) and spherical silica were each weighed out so that the spherical silica content was the amount shown in Table 1, and the mixture was stirred at room temperature with a Wonder Crusher at setting 6 for 30 seconds twice. The resulting mixture was rolled with two rolls (roll gap: set to 100 μm, roll temperature: 100° C.) to obtain a sample with a film thickness of 130 μm, which was then calcined at 340° C. or 360° C. for 15 minutes to obtain a sheet.
[0112] The spherical silica used in each example was SC6500-SQ (average particle size 2.1 μm) manufactured by Admatechs Co., Ltd., or SC6500-SQ (average particle size 2.1 μm) manufactured by Admatechs Co., Ltd. that was surface-treated with 3-aminopropyltriethoxysilane (treatment amount 1 mass%), as shown in Table 1. Example 13 used SC6500-SQ (average particle size 2.1 μm) manufactured by Admatechs Co., Ltd. that was surface-treated with 3-isocyanatepropyltriethoxysilane (treatment amount 0.3 mass%).
[0113] The fluororesin particles (PTFE) used in each example have the following properties. Average particle size: 500μm Apparent density: 460g / L Standard specific gravity: 2.17
[0114] (Comparative Example 1, Comparative Example 3, Comparative Example 7, Comparative Example 8) (Paste Extrusion) The fluororesin particles (PTFE) and spherical silica were weighed out in the proportions shown in Table 2 and mixed in a mixer in the presence of dry ice. The temperature during mixing was -10°C or lower. To the resulting mixture, 20% oil (Isopar H) was added, mixed, and aged for about 5 hours. The aged composition was preformed under a pressure of 3 MPa, and the preformed body was extruded at 40°C and 50 mm / min to obtain an extrusion sample. The extrusion sample was rolled with two rolls to obtain a sample with a film thickness of 125 μm, which was then dried at 200°C for 2 hours and calcined at 340°C or 360°C for 15 minutes to obtain a sheet.
[0115] (Comparative Example 2, Comparative Example 4 to Comparative Example 6) (Powder rolling molding) The fluororesin particles (PTFE) and spherical silica were weighed out in the prescribed amounts shown in Table 2, and the rest of the procedure was the same as in the examples to obtain a sheet.
[0116] Each of the obtained sheets was evaluated based on the following criteria. [Dk and Df] Dk and Df were measured at 25°C and 10 GHz using a split cylinder type dielectric constant / dielectric loss tangent measuring device (EM Lab).
[0117] [CTE (Coefficient of Linear Expansion)] TMA measurements were performed in tensile mode using a TMA-7100 (Hitachi High-Tech Science Corporation). A sheet cut to a length of 20 mm and a width of 5 mm was used as a sample piece. The distance between the chucks was set to 10 mm, and the CTE (coefficient of linear expansion) was calculated from the displacement of the sample from 0 to 150°C at a heating rate of 2°C / min while applying a load of 49 mN.
[0118] [Moldability] The moldability was evaluated as ◯, △, or × according to the following criteria. 〇: Sheets can be formed without wrinkles or cracks △: Wrinkles appear on the sheet ×: Cracks occurred in the sheet These results are shown in Tables 1 and 2.
[0119] [Table 1]
[0120] [Table 2]
[0121] The above results show that the sheet of the present disclosure has excellent performance in terms of a low linear expansion coefficient. [Industrial Applicability]
[0122] The sheet of the present disclosure can be particularly suitably used for high-frequency printed circuit boards.
Claims
1. A powder rolling molding composition comprising fluororesin particles and a filler, the filler content being 75 to 96.5 mass% of the total amount of the fluororesin particles and the filler, the filler containing silica, titanium oxide, magnesium oxide or a combination thereof, and components other than the fluororesin particles and the filler being 10 mass% or less.
2. 2. The powder roll molding composition according to claim 1, wherein the fluororesin particles are non-melt processable.
3. 3. The powder roll molding composition according to claim 1, wherein the fluororesin particles are polytetrafluoroethylene (PTFE).
4. 4. The powder roll molding composition according to claim 3, wherein the polytetrafluoroethylene has a standard specific gravity (SSG) of 2.0 to 2.
3.
5. 3. The powder roll molding composition according to claim 1, wherein the filler has a surface coated with a silane coupling agent.
6. 3. The powder roll molding composition according to claim 1, wherein the filler is spherical.
7. 7. The powder roll molding composition according to claim 6, wherein the spherical filler has an average particle size of 0.1 to 10 μm.
8. 3. The powder roll molding composition according to claim 1, wherein the fluororesin particles have an average particle size of 0.05 to 1000 μm.
9. A sheet or film comprising a powder roll molding composition comprising fluororesin particles and a filler, the content of the filler being 75 to 96.5 mass% of the total amount of the fluororesin particles and the filler, the filler containing silica, titanium oxide, magnesium oxide or a combination thereof, the content of components other than the fluororesin particles and the filler being 10 mass% or less, and the composition not containing a fiber reinforcing material.
10. The sheet or film according to claim 9, having a thickness of 5 to 250 μm.
11. 11. The sheet or film according to claim 9 or 10, having a relative dielectric constant (Dk) of 3.5 or less, a dielectric loss tangent (Df) of 0.0014 or less, and a coefficient of linear expansion (CTE) of 40 ppm / K or less at 10 GHz.
12. A method for producing a sheet or film, comprising the steps of: mixing fluororesin particles with a filler containing silica, titanium oxide, magnesium oxide or a combination thereof such that the content of the filler is 75 to 96.5 mass% of the total amount of the fluororesin particles and the filler, and such that the content of components other than the fluororesin particles and the filler is 10 mass% or less; and forming the mixture into a film by powder rolling molding.
13. The method for producing a sheet or film according to claim 12, characterized in that the film is formed using a composition consisting essentially of fluororesin particles and a filler.
14. A metal laminate comprising a metal layer and the sheet or film according to claim 9 or 10 as essential layers.
15. The metal laminate of claim 14, wherein the metal layer is a copper foil.
16. A circuit board comprising the metal laminate according to claim 15.
Citation Information
Patent Citations
Electric base body material
JP1988259907A
Sheet forming composition, filler-containing fluororesin sheet, and method for producing the filler-containing fluororesin sheet
JP2011153254A
PTFE paste extrusion molding, method for producing the same, PTFE composition for PTFE paste extrusion molding, and method for producing the composition
JP2012219190A
Printed wiring board for high frequency use
JP2015008260A
Substrate and metal laminate
WO2021024883A1